A exceção do contrato não cumprido fundada na violação de dever lateral - Pereira, Paulo Sérgio Velten (2008)
This research aims the investigation of the possibility of arguing the exception of the breach of contract (exceptio non adimpleti contractus) due to the violation of the lateral duty of conduct. The choice for preparing this study has been motivated by the verification that the open system of the Brazilian Civil Code of 2002 has given the interpreter the possibility of filling the legislation s general clauses with the fundamental values of the Constitution and the civil Law, in a way that those values become applied in interprivate relations. Among the general clauses, one of great importance is the objective good-faith clause, which constitutes a mandatory clause for the contracting parties. By researching the national and foreign literature concerning the changes in the field of the Law of Obligations, it has been concluded that from the general clause of objective good-faith derives the lateral duties, which grants complexity to the obligational relations, widens the base of default and generates effects that move beyond the mere duty to compensate damages and the possibility of termination of contract. The study s main hypothesis is that the reactive function the general clause of objective good-faith constitutes enough grounds to restrict the subjective right and control the abuse of a contract party who demands the other party s fulfilment of the contract without even respecting the lateral duties in the first place. This hypothesis gives a new approach to the exceptio non adimpleti contractus, highlighting the institute as an instrument for preserving the contractual balance and justice